Language and alexithymia: Evidence for the role of the inferior frontal gyrus in acquired alexithymia - Hobson, H; Hogeveen, J; Brewer, R; Catmur, C; Gordon, B; Krueger, F; Chau, A; Bird, GP; Grafman, J (Elsevier, 2018)
The clinical relevance of alexithymia, a condition associated with difficulties identifying and describing one’s own emotion, is becoming ever more apparent. Increased rates of alexithymia are observed in multiple psychiatric conditions, and also in neurological conditions resulting from both organic and traumatic brain injury. The presence of alexithymia in these conditions predicts poorer regulation of one’s emotions, decreased treatment response, and increased burden on carers. While clinically important, the aetiology of alexithymia is still a matter of debate, with several authors arguing for multiple ‘routes’ to impaired understanding of one’s own emotions, which may or may not result in distinct subtypes of alexithymia. While previous studies support the role of impaired interoception (perceiving bodily states) in the development of alexithymia, the current study assessed whether acquired language impairment following traumatic brain injury, and damage to language regions, may also be associated with an increased risk of alexithymia. Within a sample of 129 participants with penetrating brain injury and 33 healthy controls, neuropsychological testing revealed that deficits in a non-emotional language task, object naming, were associated with alexithymia, specifically with difficulty identifying one’s own emotions. Both region-of-interest and whole-brain lesion analyses revealed that damage to language regions in the inferior frontal gyrus was associated with the presence of both this language impairment and alexithymia. These results are consistent with a framework for acquired alexithymia that incorporates both interoceptive and language processes, and support the idea that brain injury may result in alexithymia via impairment in any one of a number of more basic processes.